2015
DOI: 10.1111/asj.12469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation with cellooligosaccharides on growth performance of weaned calves on pasture

Abstract: We conducted two feeding experiments to evaluate the effects of cellooligosaccharide (CE) supplementation on growth performance in grazing beef calves. Calf sex and age and duration of the experimental period differed between the experiments. Experiment 1 (10 weeks) used 5.6-month-old castrated males; Experiment 2 (13 weeks) used 3.9-month-old females. Eight Japanese Black calves were assigned to either a control group (CON) or an experimental group (CE) fed CE at a rate of 10 g/day mixed with concentrate. Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…We reported on the effects of a cellooligosaccharides dietary supplement derived from enzymatic digestion of plant cellulose and consisting of glucose with β‐1‐4 linkages on weaned grazing calves. Our results showed that the cellooligosaccharide supplement promoted growth in a period subsequent to the period of supplement provision (Kido et al, ). The major advantage of supplementing a calf's diet with prebiotics (dietary nondigestible oligosaccharide) is that it enhances the number of beneficial intestinal bacteria involved in carbohydrate fermentation for improving the health, performance, and intestinal biota of calves (Gaggìa, Mattarelli, & Biavati, ; Quezada‐Mendoza, Heinrichs, & Jones, ; Uyeno et al, ).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…We reported on the effects of a cellooligosaccharides dietary supplement derived from enzymatic digestion of plant cellulose and consisting of glucose with β‐1‐4 linkages on weaned grazing calves. Our results showed that the cellooligosaccharide supplement promoted growth in a period subsequent to the period of supplement provision (Kido et al, ). The major advantage of supplementing a calf's diet with prebiotics (dietary nondigestible oligosaccharide) is that it enhances the number of beneficial intestinal bacteria involved in carbohydrate fermentation for improving the health, performance, and intestinal biota of calves (Gaggìa, Mattarelli, & Biavati, ; Quezada‐Mendoza, Heinrichs, & Jones, ; Uyeno et al, ).…”
Section: Introductionsupporting
confidence: 61%
“…All calves were allowed for suckling in the pre‐weaning period and were fed a commercial concentrate feed (consisting of 155 g/kg of crude protein, 30 g/kg of crude fat, and 72.5% total digestible nutrients (TDN), Snow Brand Seed Co., Ltd) from 4 weeks before weaning at a daily maximum of 2,000 g. The method used for weaning of all experimental calves was abrupt separation from their mothers. In Experiment 1, the experimental groups were fed cellooligosaccharides at a rate of 10 g/day, mixed with the concentrate feed given during 20 weeks of the experiment, in accordance with the procedure applied in our previous study (Kido et al, ). In Experiment 2, kraft pulp (hardwood kraft pulp, Nippon Paper Industries Co., Ltd) was fed to the calves in the KRA group at a rate of 10% of the total digestible nutrition basis for replacement of the concentrate feed given during 16 weeks of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have reported these oligosaccharides as potential prebiotics that could regulate intestinal bacterial composition, modify fermentative processes, and possibly improve host health (Cheng et al 2017;Jiao et al 2014;Zhao et al 2012). Due to the β-1,4-glucosidic linkage between glucose monomers, cello-oligosaccharides are resistant to host digestive enzymes and in turn serve as a substrate for intestinal microbiota (Hasunuma et al 2011;Kido et al 2016;Otsuka et al 2004). The endo-β-1,4-glucanases characterized in this work could be used in the development of value-added products.…”
Section: Discussionmentioning
confidence: 99%